"I changed and hid my old ways": How social rejection and social identities shape well‐being among ex‐prisoners. Issue 5 (21st February 2019) - Kyprianides, Arabella; Easterbrook, Matthew J.; Cruwys, Tegan
Abstract: Being a member of a rejected group negatively affects well‐being but can also increase group identification, which can have positive effects on well‐being. However, this rejection‐identification model has never been investigated among the highly stigmatized group of ex‐prisoners. Furthermore, the potential buffering role of multiple group memberships has never been investigated within the rejection‐identification model. We conduct a novel investigation of a combined rejection‐identification and social cure model of group‐based rejection among ex‐prisoners. A survey of 199 ex‐prisoners found that experiencing group‐based rejection was associated with poorer well‐being and increased ex‐prisoner identification. However, identification as an ex‐prisoner magnified, rather than buffered, the relationship between rejection and reduced well‐being. Furthermore, the negative relationship between rejection and well‐being was particularly pronounced among ex‐prisoners with a higher number of group memberships. Ex‐prisoners with a greater number of group memberships experienced greater levels of rejection, suggesting group memberships increase their exposure to rejection. We therefore provide evidence of a boundary condition for the social cure properties of groups. Among members of strongly rejected social groups, multiple group memberships can be a social curse rather than social cure.